Tensile And Impact Properties Of Mineral Fillers Filled Poly(Lactide) Acid Composites - Yu, Kai Chun (Universiti Sains Malaysia, 2022)
Usage of polymer material in food packaging field had been maintained from last decades until now. Biodegradable polymer had been investigated to replace original petrochemical polymer due to its affection to the environment. Polylactide Acid is one of the common biodegradable polymers that had been investigate for the usage of food packaging material. But PLA contains weakness on mechanical properties that affect the application of it. The aim of this research works is to investigate the effect of different loading of Polyethylene Glycol (PEG) and mineral fillers (Calcium Carbonate, Nepheline Syenite and Sibelite) on the mechanical properties of PLA. Fabrication of the composite is done by drying the materials in 50℃ and melt-mixed with twin screw extruder. The materials produced were shape forming by using injection molding and hot press to form shape for tensile testing and impact testing. The particle of mineral fillers was characterized by Particle Size Analyzer (PSA) and Scanning Electron Microscope (SEM). The result showed that the addition of Calcium Carbonate causing increasing in tensile properties from 15wt% to 45wt% reached maximum at 36.47 MPa while addition of the other two fillers causing decreasing with increasing in fillers loading which reach 18.08 MPa (Nepheline Syenite) and 17.71 MPa (Sibelite). The elongation at break decreased for all three fillers when the filler loading increase to 45wt% with value 5.25% (CaCO3), 2.94% (NS) and 3.41% (Sibelite). The tensile modulus of NS and Sibelite composite decreased with the increase of filler loading but increased for CaCO3 composite.